In Silico DFT (Density Functional Theory) Study of Chemosensor Selectivity of 3-Oxo-3H-Benzo[f]chromen-2-Carboxylic Acid (ABKK) on Sodium Metal Ion Using FMO (Frontier Molecular Orbital) Analysis - Jamaludin Al-Anshori; Ajar Faflul Abror; Juliandri Juliandri; Agus Safari; Ace T. Hidayat (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
The chemosensor selectivity of 3-oxo-3H-benzo[f]chromen-2-carboxylic acid (ABKK) toward Na+ metal ionhas been successfully studied in silico using FMO (Frontier Molecular Orbital) analysis method. The geometry of the ABKK structure was optimized by the DFT (Density Functional Theory) method with a function/basis set: M06/6-31G (d, p). Afterward, the electronic properties of the ABKK structure before and after binding to sodium ion were analyzed and compared with the ABKK+other metal ion structures representing valence charges 1-3 and within the constraints of the basis set used. The results of geometry optimization showed that 1ABKK+Na+ has a more positive frequency/minima than 2ABKK+Na+ with interaction energies of 145 and 200.5 kcal/mol, respectively. Ignoring the role of solvents, FMO analysis revealed that the bandgap energy of fluorophore and receptor interactions (∆E LUMO Fl-Rs 1ABKK+Na+) and (∆E HOMO Fl-Rs 2ABKK+Na+) were 0.631 and 0.336 eV, correspondingly. In addition, the bandgap energy of fluorophore/∆E Fl 1ABKK+Na+ and 2ABKK+Na+ were calculated at 4.347 and 4.362 eV. Comparing those two types of bandgap energies with the bandgap belonging to ABKK+other metal ions, the excitation, and PET (Photoinduced Electron Transfer) processes were estimated to be relatively favorable experienced by 2ABKK+Na+. Finally, the selectivity of ABKK toward sodium metal ions from the computational calculations was relatively in agreement with the laboratory experimental results.